E – Learning Training Course on “Date Palm Value Chain Analysis, Management, and Market Linkages in the GCC Countries” - Dhehibi, B.; Ibrahim, A. O.; Hilali, M. E.; Niane, A. A.; Nejatian, A. (2021)
Value chain encompasses the full range of activities and services required to bring a product or service from its conception to sale in its final markets—whether local, national, regional, or global. Value chains include input suppliers, producers, processors, and buyers, as well as the support services and enabling environments that form a dynamic market system. It is in the frame of the APRP-ICARDA date palm project named “Developing sustainable production systems for date palm in the Gulf Cooperation Council countries” activities, an E-learning training course on “Date Palm Value Chain Analysis, Management and Market Linkages” is planned to be delivered. The E-learning training course is aimed at equipping the participants with principles and practices of the date palm value chain and market linkages management. The course is designed to enable the participants from Kuwait, United Arab Emirates, Qatar, Saudi Arabia, Oman, and Bahrain to effectively contributing to the implementation of the socio-economic activities planned in the frame of the outlined project.